(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
Albert Camus has been a central figure in world culture for much of the 20th century. His polyphonic work combines metaphysical, anthropological and political problems. In this work we dwell on the "images" that disturb the soul of the writer and that, therefore, structure all his work. The tender and lost look of his mother, the child who dies in the streets of Algiers, the wooden piano that enlivens the sad day in the concentration camp are just some of the scenes that go through the great work. Our thesis is that they not only modulate the sensitivity of the great writer, but also give structure and motivation to his fundamental philosophical categories: absurdity and rebellion.